Characterization of turbulence anisotropy, coherence, and intermittency at a prospective tidal energy site: Observational data analysis. (April 2015) - McCaffrey, Katherine; Fox-Kemper, Baylor; Hamlington, Peter E.; Thomson, Jim
Abstract: As interest in marine renewable energy increases, observations are crucial for understanding the environments that prospective turbines will encounter. Data from an acoustic Doppler velocimeter in Puget Sound, WA are used to perform a detailed characterization of the turbulent flow encountered by a turbine in a tidal strait. Metrics such as turbulence intensity, structure functions, probability density functions, intermittency, coherent turbulence kinetic energy, anisotropy invariants, and a new scalar measure of anisotropy are used to characterize the turbulence. The results indicate that the scalar anisotropy magnitude can be used to identify and parameterize coherent, turbulent events in the flow. An analysis of the anisotropy characteristics leads to a physical description of turbulent stresses as being primarily one- or two-dimensional, in contrast to isotropic, three-dimensional turbulence. A new measure of the anisotropy magnitude is introduced to quantify the level of anisotropic, coherent turbulence in a coordinate-independent way. These diagnostics and results will be useful for improved realism in modeling the performance and loading of turbines in realistic ocean environments. Highlights: We characterize turbulence from acoustic Doppler velocimeter observations. We analyzed autocorrelations, structure functions, and intermittency from pdfs. We compare turbulent events defined by turbulence intensity, TKE, and coherent TKE. We quantify and map anisotropy using eigenvalues of the anisotropy tensor. A tensor-invariant anisotropy magnitude correlates best with correlation scale.